Seaweed in the peruvian diet - Noriega Cardó, Cristóbal (2017)
It is said that Peruvians lived many years with their backs turned to the sea, perhaps rightly so. We have notused and appreciated everything that our sea produces. In this paper we will give value to a product the world hasmostly relegated to the background, but we hope it will perhaps be revalued: seaweed. In this article, we willbriefly discuss the history of seaweed in Peru and its cultural use and importance prior to the Spanish conquest.Before the conquest of the coastal towns, seaweed was consumed with dry-salted fish, and used as currency toacquire agricultural products in commercial exchange with communities from the Peruvian Andes. Additionally,we will discuss the importance of seaweed in the human diet and share its nutritional value through nutritionaltables. We will provide some simple recipes that will allow the integration of seaweeds in meals for the family;from dinner to children’s lunches. We will cover basic seaweed taxonomy and share with the general public how to identify and best use different classes of seaweeds. Fortunately, several ofthese algae are readily available to the general public; they are sold in local markets as fresh weeds («yuyo»Quechua for weeds) as well as semi-dry and dry-salted («cochayuyo» Quechua for seaweeds). Curiously,people that reside in the towns closer to the Peruvian mountain range consume these algae in the popularspicy seaweed stew dish known as «Picante de Cochayuyo». However, the inhabitants of the Peruviancoastal towns have no documented integration of seaweed as the main ingredient for the recipes they cookand consume most often.